2023
DOI: 10.3389/fcimb.2023.1255083
|View full text |Cite
|
Sign up to set email alerts
|

Response mechanisms to acid stress promote LF82 replication in macrophages

Ting Yao,
Yu Huang,
Zimeng Huai
et al.

Abstract: BackgroundAdherent–invasive E. coli (AIEC) LF82 is capable of adhering to and invading intestinal epithelial cells, as well as replicating within macrophages without inducing host cell death.MethodsWe compared the transcriptomics of LF82 at pH=7.5 and pH=5.8 by RNA-sequencing, and qRT-PCR verified differentially expressed genes (DEGs). The deletion mutants of DEGs in the treatment group (pH=5.8) compared to the control group (pH=7.5) were constructed by λ recombinant. The replication differences between the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Our previous study demonstrated that the neutralization of the acidic environment in macrophages with NH 4 Cl or CQ resulted in a reduction in LF82 replication by 3.3-fold and 4.2-fold, respectively. 39 Whereas the replication ability of Δ rstA or Δ rstAB was unaffected in NH 4 Cl or CQ-treated Raw 264.7 cells compared with WT ( Figure 6i,j ). These results indicate that RstAB promotes the replication of LF82 in response to the acidic environment of macrophages.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Our previous study demonstrated that the neutralization of the acidic environment in macrophages with NH 4 Cl or CQ resulted in a reduction in LF82 replication by 3.3-fold and 4.2-fold, respectively. 39 Whereas the replication ability of Δ rstA or Δ rstAB was unaffected in NH 4 Cl or CQ-treated Raw 264.7 cells compared with WT ( Figure 6i,j ). These results indicate that RstAB promotes the replication of LF82 in response to the acidic environment of macrophages.…”
Section: Resultsmentioning
confidence: 95%
“…In our previous study, we found that the expression of rstA and rstB was significantly upregulated in the transcriptome under acid treatment conditions, mimicking the acidic environment of macrophages, indicating that acid may activate the expression of rstA and rstB . 39 qRT-PCR was performed to verify the transcriptome results. rstA and rstB were significantly upregulated by 3.4-fold and 2.1-fold in the acid-treated group compared with the control group, respectively ( Figure 6(a,b) ).…”
Section: Resultsmentioning
confidence: 99%
“…As a matter of fact, it has been reported that biomechanical microenvironments around host cells can exert a crucial impact on bacterial-cell interactions such as binding of adhesins to host cell receptors 40 and bacterial infection of epithelial cells and intracellular accumulation of antibiotics 41 . It is very likely that quantitative studies on the regulation of biophysical/biomechanical microenvironments on the bacterial-cell interations provides new ideas for developing of host-acting antibacterial therapies 36,[42][43] .…”
Section: Introductionmentioning
confidence: 99%